THE COVERAGE OF FORCED MIGRATION IN UKRAINIAN ONLINE MEDIA (2022-2023) - Shutiak, Lilia (NGO “German-Ukrainian Dialogue” (Augsburg, Germany), 2023)
With the beginning of the full-scale Russian invasion, many Ukrainian journalists radically changed the vector of their activities and switched from covering political, economic and cultural topics to covering stories of internally displaced persons, relocated businesses and everything related to military issues. This issue first appeared in the Ukrainian media back in 2014, and more recently (since February 2022) it has gained more and more resonance and interest among the target audience.
Keywords: FORCED MIGRATION; UKRAINIAN ONLINE MEDIA